The social context of the Book of Job - Roper, Leon A. (Verbum et ecclesia, 2005)
Although much has been written about the Book of Job, no consensus exists among scholars with regard to issues such as the dating and origins of this book. In this article the controversies surrounding the social context of the book of Job are discussed. This is followed by an attempt to reconstruct a possible socio-theological context for this book. In doing this, special attention will be given to the writer’ s possible relationship with the mainstream theological tradition of his day. This will be done by considering the possible aim of the "implied" author in constructing the book as well as the ways in which he has gone about achieving this aim. It is concluded that the implied author aimed to critically comment on the way in which the orthodox wisdom teachers of his time had clung to the traditional dogma of divine retribution. In doing this, this author seems to have employed various indirect techniques such as the use of a dramatic narrative to convey his message.